Graphene Oxide: Surface Activity and Two-Dimensional Assembly - Kim, Franklin; Cote, Laura J.; Huang, Jiaxing (Advanced materials (Weinheim), 2010)
Graphene oxide (GO) is a promising precursor for preparing graphene‐based composites and electronics applications. Like graphene, GO is essentially one‐atom thick but can be as wide as tens of micrometers, resulting in a unique type of material building block, characterized by two very different length scales. Due to this highly anisotropic structure, the collective material properties are highly dependent on how these sheets are assembled. Therefore, understanding and controlling the assembly behavior of GO has become an important subject of research. In this Research News article the surface activity of GO and how it can be employed to create two‐dimensional assemblies over large areas is discussed. Graphene oxide (GO) has recently become an actively explored material for graphene‐related electronics applications. Due to its highly anisotropic structure, the collective properties of the sheets are strongly dependent on how they are assembled; therefore, understanding and controlling the assembly of GO sheets becomes an important challenge. In this Research News article, the amphiphilic nature of GO and how it can be utilized for preparing 2D assemblies (see figure) is discussed.